Anti-corruption measures the Japanese way: prevention matters. Issue 1 (5th January 2015) - Jon S.T. Quah, Dr; Chilik Yu, Professor; Oyamada, Eiji
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to analyze recent Japanese corruption prevention mechanisms and assess the efforts of the Japanese government in winning public trust. Design/methodology/approach – This paper discusses public sector corruption in Japan at an institutional level through a study of its features and current status. It then analyzes and evaluates the effectiveness of corruption prevention measures and the public perceptions of these measures. The paper concludes with a discussion on whether such measures can be adopted by other countries. Findings – Recent preventive measures in Japan are effective in decreasing corruption opportunities, but not in enhancing the public trust of the government. Major findings are: first, Japan is the only Asian country without a dedicated anti-corruption agency (ACA); second, there is more emphasis on corruption prevention in the anti-corruption measures; third, the government is concerned with initiating measures to prevent the further erosion of public trust when corruption occurs; fourth, while preventive measures such as public disclosure and whistle-blower protection acts are in place, public awareness of their existence is still lacking and the usage of these systems is limited; fifth, more efforts are placed on prevention through the promotion of government transparency and accountability and public sector ethics education rather than penalizing the corrupt offenders; and sixth, though efforts to minimize amakudari practices are made, lack of political will and its sustainability prevents further reform. Originality/value – This paper will be useful for scholars, policy-makers, and anti-corruption practitioners interested in learning how Japanese government practices prevent corruption.